Analisa Faktor Internal, Eksternal dan Resource – Based View Untuk Strategi PT XYZ dalam Memenangkan Persaingan dalam Industri Timbangan - Teguh Halim (Universitas Tarumanagara, 2020)
A qualitative research about how PT XYZ (weighing industry company) implemented a strategy by analysing internal factor (strength and weakness), external factor (opportunity and threat) using Resource – Based View and SWOT Analysis.The conclusion of this research is PT XYZ implement Forward Integration, Market Development and Product Development as their strategy in the future to maximize the company strength.